Molecular evolution of vision-related genes may contribute to marsupial photic niche adaptations - Tian, Ran; Guo, Han; Jin, Zhihong; Zhang, Fan; Zhao, Junpeng; Seim, Inge (Frontiers in Ecology and Evolution, 2022)
Vision plays an essential role in the life of many animals. While most mammals are night-active (nocturnal), many have adapted to novel light environments. This includes diurnal (day-active) and crepuscular (twilight-active) species. Here, we used integrative approaches to investigate the molecular evolution of 112 vision-related genes across 19 marsupial genomes representing most marsupial orders. We found that four genes (GUCA1B, GUCY2F, RGR, and SWS2) involved in retinal phototransduction likely became functionally redundant in the ancestor of marsupials, a group of largely obligate nocturnal mammals. We also show evidence of rapid evolution and positive selection of bright-light vision genes in the common ancestor of Macropus (kangaroos, wallaroos, and wallabies). Macropus-specific amino acid substitutions in opsin genes (LWS and SWS1), in particular, may be an adaptation for crepuscular vision in this genus via opsin spectral sensitivity tuning. Our study set the stage for functional genetics studies and provides a stepping-stone to future research efforts that fully capture the visual repertoire of marsupials.